Applying The "Bingo" Game Method in Teaching Vocabulary at Nurul Ulum Islamic Intermediate School Poncokosumo Malang - Afifah Shofia Faradisa; Danial Hilmi (Abjadia, 2023)
In vocabulary learning, students are expected to be able to pronounce vocabulary according to the correct output (makhraj), understand the meaning and derivation of the word, explain its meaning in the correct language structure, and use the right words in the correct sentence context. However, there are problems that occur in vocabulary learning at MTs Nurul Ulum Poncokusumo Malang Regency, including the relatively low number of vocabularies mastered by students, some students' pronunciation is not good and correct, and some students have difficulty in understanding and applying vocabulary into sentences. This study aims to describe and determine the effectiveness of the application of bingo game media in vocabulary learning at Mts Nurul Ulum Poncokusumo Malang Regency. The approach used by the researcher is a quantitative approach with an experimental method in the form of a quasi-experimental design, namely a non-equivalent control group design. The results of the study are as follows: 1) multi-disciplinary learning with bingo game media uses the stages of exploration, bingo organization, elaboration, confirmation, and material strengthening. 2) Through observation, it can be seen that students' memorization of vocabulary is increasing and they are able to mention more vocabulary than usual. The results of the t-test indicate that there is a significant difference between the experimental group and the control group because the t-count value (3.469) is greater than the t-table (2.021). Therefore, it can be concluded that the use of bingo game media is quite effective in vocabulary learning at MTs Nurul Ulum Poncokusumo Malang Regency.